VIBROACOUSTIC SYSTEM FOR MEASUREMENT OF THE TOUCHDOWN OF A LIGHT AIRCRAFT - Damian SALA; Jerzy MOTYLEWSKI; Arkadiusz MRÓZ; Piotr PAWŁOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
Aircraft touchdown is one of the most difficult and dangerous phases of a flight. The paper presents an aerial light aircraft, prepared and produced by vibroacoustic tests, using an aircraft landing and landing monitoring system (AVI). The concept is based on the use of an ultrasonic transceiver head and vibration transducer, together with an appropriate signal processing and analysis system. The system measures the touchdown speed and altitude of the aircraft in the final phase of the flight and determines the level of load transmitted to the aircraft during the landing. Thanks to data archiving, it allows for better estimation of the wear rate of the structure, which is important in determining the causes of possible malfunction. It can be used with light and ultralight aircraft and, after adaptation, in unmanned aircraft. It can also be used to evaluate the art of piloting during landing.